Unveiling size‐fluorescence correlation of organic nanoparticles and its use in nanoparticle size determination - Wu‐Jie Guo; Shixiang Ma; Hui Wang; Lu Qiao; Lei Chen; Chenyu Hong; Bin Liu; Xiaoyan Zheng; Hui‐Qing Peng (Aggregate, 2024)
Abstract Quantitatively establishing the correlation between nanoparticle size and fluorescence is essential for understanding the behavior and functionality of fluorescent nanoparticles (FNPs). However, such exploration focusing on organic FNPs has not been achieved to date. Herein, we employ the use of supramolecular polymeric FNPs prepared from tetraphenylethylene‐based bis‐ureidopyrimidinone monomers (bis‐UPys) to relate the size to the fluorescence of organic nanoparticles. At an equal concentration of bis‐UPys, a logarithmic relationship between them is built with a correlation coefficient higher than 0.96. Theoretical calculations indicate that variations in fluorescence intensity among FNPs of different sizes are attributed to the distinct molecular packing environments at the surface and within the interior of the nanoparticles. This leads to different nonradiative decay rates of the embedded and exposed bis‐UPys and thereby changes the overall fluorescence quantum yield of nanoparticles due to their different specific surface areas. The established fluorescence intensity‐size correlation possesses fine universality and reliability, and it is successfully utilized to estimate the sizes of other nanoparticles, including those in highly diluted dispersions of FNPs. This work paves a new way for the simple and real‐time determination of nanoparticle sizes and offers an attractive paradigm to optimize nanoparticle functionalities by the size effect.